Knowledge Integration: In-service training for content professors teaching through English - Griffith-Bourn, Mary Margaret (My University, 2018)
When we move into the realm of integrating content and language in higher education (ICLHE), we expand the model to include attitudes, language as well as learning. Kevin Haines (2017) in a conference on the role of language centers at the university suggested that much had been done with regard to principles and policies across Europe in plurilingual programs; however, many aspects of practice still needed closer examination. Rubio & Hermosin (2010) describe content professors as 'reluctant' ; Fortanet-Gomez (2012) highlighted the need for a 'closer follow-up' when assessing bilingual instruction at the university. It is with this perceived reluctance, with a decided follow-up and, ultimately, with purposeful practice in mind that we will center the discussion about in-service training at the university. In order to provide content professors with the support they need when facing bilingual instruction in their classrooms, we begin not by telling them what they need, rather by asking how we can help.
Datos comparativos entre las facultades de Turismo e Informática de sus programas bilingües
Keywords: Lingüística - Congresos; Bilingual instruction; Action research; Professional Development; Lingüística aplicada; Interacción en el aula bilingüe